Vesicosalpingo Fistula: A Case Presentation And Review of The Literature. Issue 6 (November 2016) - Maloney, Taylor G.; Kavanagh, Alex; Khavari, Rose
Abstract : Objectives: To describe a case presentation and perform a review of the literature on vesicosalpingo fistulas. Methods: An otherwise healthy 32 year-old patient was referred to urology with symptoms of persistent abdominal bloating and urine leakage from the vagina after abdominal conversion of laparoscopic hysterectomy. Two fistula tracts were identified in the bladder during preoperative cystoscopy. The tracts were cannulated with temporary ureteral catheters, and the patient underwent a robotic-assisted laparoscopic repair of a vesicosalpingo and a vesicovaginal fistula. Results: The patient was discharged on the first postoperative day with an indwelling urinary catheter. A follow-up cystogram performed on the 14th postoperative day demonstrated no evidence of extravasation. There was no evidence of recurrence at a 4-month follow-up visit. This is the first reported robot-assisted laparoscopic repair of a vesicosalpingo fistula and the fifth reported case of a vesicosalpingo fistula in the literature. This is the first reported case of separate vesicosalpingo and vesicovaginal fistulas presenting concurrently in a single patient. Conclusions: This case presentation with 2 separate fistula tracts emanating from the bladder demonstrates the need to meticulously evaluate each individual fistula tract in order to successfully visualize and address all fistula tracts present in order to mitigate failures and the need for reoperation. Abstract : This article describes a case of concomitant vesicosalpingo and vesicovaginal fistula that presented with continuous urinary leakage following laparoscopic converted to abdominal hysterectomy.